Efisiensi Mikropropagasi Pisang Kepok Amorang melalui Modifikasi Formula Media dan Temperatur - Supriati, Yati (Jurnal AgroBiogen, 2010)
Micropropagation Efficiency of Banana cv KepokAmorang through Modifications of Culture Media andIncubation Temperature. Yati Supriati. The budlessbanana cv Kepok Amorang is potentially commercializeddue to its sweet taste and does not have flower bud, hencereduced the potential of being infected by the blood diseasepathogen. Enhancement of banana industry needs continuoussupplies of large number banana seedlings. In vitroculture enable the production of seedlings in a large scale,uniform, quick. The research aims: (1) to formulate anefficient medium for in vitro multiplication of cv KepokAmorang shoot, (2) to identify efficient growth environmentfor in vitro culture of cv Kepok Amorang, and (3) to formulatean efficient culture medium for roots inductions of cvKepok Amorang. The plant material used was in vitro cultureof Kepok cv Amorang, 2 cm in height without leaf and root.The media formulation for shoot multiplication were fullstrength, half strength, one fourth strength MS media,supplemented with either 1, 3, or 5 ppm IBA. On optimizationstep, the media tested were MS, Knop, Knop andHeller, Hyponex N, Growmore N, and Rosasol N containingof 1 ppm BA. The explants were incubated in culture roomwith 8, 12, and 16 hours photoperiod with temperatures 30oC(non air conditioned) and 25oC (air conditioned). The rootinduction trial was done using MS, Knop, Knop and Heller,Hyponex N, Growmore N, and Rosasol N media containingof 1 ppm and 3 ppm IBA. The results showed that the bestmedium formula for shoot multiplication was Â¼ MS + 1 ppmIBA. The best incubation condition was 16 hours photoperiodsat 30oC. The best media for root induction wasHyponex 2 g/l + 1 ppm IBA. This culture method reducedcost by Rp 261.7 per plantlet through efficiency of mediaformulation and electricity use.